Phytochemical analysis, radical scavenging and glioblastoma U87 cells toxicity studies of stem bark of buckthorn (Rhamnus pentapomica R. Parker) - Yaseen Ur Rehman; Arshad Iqbal; Gowhar Ali; Ghallab Alotaibi; Alshebli Ahmed; Muhammad Ayaz (BMC Complementary Medicine and Therapies, 2024)
Abstract Background During the past two decades, the correlation between oxidative stress and a variety of serious illnesses such as atherosclerosis, chronic obstructive pulmonary disease (COPD), Alzheimer disease (AD) and cancer has been established. Medicinal plants and their derived phytochemicals have proven efficacy against free radicals and their associated diseases. The current work was aimed to evaluate the phytochemical constituents of Rhamnus pentapomica R. Parker via Gas Chromatography-Mass Spectrometry (GC–MS) and its antioxidant and anti-glioblastoma potentials. Methods The bioactive compounds were analysed in Rhamnus pentapomica R. Parker stem bark extracts by GC–MS analysis, and to evaluate their antioxidant and anti-glioblastoma effects following standard procedures. The stem bark was extracted with 80% methanol for 14 days to get crude methanolic extract (Rp.Cme) followed by polarity directed fractionation using solvents including ethyl acetate, chloroform, butanol to get ethyl acetate fraction (Rp.EtAc), chloroform fraction (Rp.Chf) and butanol fraction (Rp.Bt) respectively. Antioxidant assay was performed using DPPH free radicals and cell viability assay against U87 glioblastoma cancer cell lines was performed via MTT assay. Results In GC-MS analysis, thirty-one compounds were detected in Rp.Cme, 22 in Rp.Chf, 24 in Rp.EtAc and 18 compounds were detected in Rp.Bt. Among the identified compounds in Rp.Cme, 9-Octadecenoic acid (Z)-methyl ester (7.73%), Octasiloxane (5.13%) and Heptasiloxane (5.13%), Hexadecanoic acid, methyl ester (3.76%) and Pentadecanoic acid, 14-methyl-, methyl Ester (3.76%) were highly abundant.. In Rp.Chf, Benzene, 1,3-dimethyl- (3.24%) and in Rp.EtAc Benzene, 1,3-dimethyl-(11.29%) were highly abundant compounds. Antioxidant studies revealed that Rp.Cme and Rp.EtAc exhibit considerable antioxidant potentials with IC50 values of 153.53 μg/ml and 169.62 μg/ml respectively. Both fractions were also highly effective against glioblastoma cells with IC50 of 147.64 μg/ml and 76.41ug/ml respectively. Conclusion Phytochemical analysis revealed the presence of important metabolites which might be active against free radicals and glioblastoma cells. Various samples of the plant exhibited considerable antioxidant and anti-glioblastoma potentials warranting further detailed studies.